The chain of bits in the light of authenticity: binary contente as a central elemento of the composition of nato-digital archival record - Rabelo, Natália Bruno (2022)
This article is dedicated to the analysis of the theorical foundations of Computer Science regarding the architecture of computers in the scope of transmission of digital archival records and of Archival Science related to the authenticity of digital records. This link between the two areas arises the Computational Archival Science, since the end of the 20th century there has been a growth in the adoption and management of digital records. However, the architecture of the native-digital archival records still remains a poorly explored study object, which demonstrates the fundamental relationship with the binary content that is pointed out in the literature as vulnerable to loss of form and content data according to events, and, therefore, a challenge for digital preservation in the Archival Science scope. Therefore, it is worth reflecting on the following question: “what is the relationship of the binary content with the authenticity of the native-digital archive document? This qualitative research was operationalized through bibliographic research of Brazilian and foreign works of Archival Science and Computer Science that sequentially address digital records, authenticity, computer architecture and binary arithmetic. The results suggested that the form of the record is not necessarily linked to authenticity and that, because the binary content is always subject to changes that jeopardize its integrity and, at the same time, is the representative element of the record’s originality that must be preserved in a safe of tampering environment to authenticate record’s copies that had its digital complement compromised.